Perubahan morfologi gigi permanen akibat bruksisma (Morphological changes of permanent teeth due to bruxism) - Asmawati Asmawati; Bahruddin Thalib; Rudin Tamril (DiscoverSys Inc., 2014)
Grinding or clenching teeth during sleep or unconsciously called bruxism. Bruxism is a bad habit that is occured inalmost people, from children to adults. Bruxism closely related to changes in tooth morphology due to erosion of toothsurfaces, especially on the occlusal area. This study aimed to determine the morphological changes of permanent teethdue to bruxism. By using the method of observational analytic and cross-sectional design, the sample set in adults whoexperience bruxismas many as 69 samples; 23 samples do bruxismand 46 samples do not do bruxism. The results showedthat the morphological changes on occlusal and incisal surfaces of the teeth in 78.3% of samples undergo bruxism, andsamples do not undergo morphological changes as much as 21.7%. 6.5% of samples who did bruxism had dentalmorphology changes, and the prevalence is higher in men than women. With the chi-square test, it is known that thereis significant effect (p<0.05) of bruxism on morphological changes of permanent teeth. It was concluded that bruxismaffect the morphological changes of permanent teeth.